2019
DOI: 10.3390/ijms20225769
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Trait Induces Oxidative Damage on Plasmodium falciparum Proteome at Erythrocyte Stages

Abstract: The presence of hemoglobin A-S (HbAS) in erythrocytes has been related to the high production of reactive oxygen species (ROS) and an increased in intracellular oxidative stress that affects the progress of Plasmodium erythrocytic cycle life and attenuates its serious clinical symptoms. Nevertheless, oxidative effects on P. falciparum proteome across the intraerythrocytic cycle in the presence of HbAS traits have not been described yet. Here, an immune dot-blot assay was used to quantify the carbonyl index (C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Further, it has been shown that parasites are fragile and killed by these HbS polymers. A compelling cause of reduced parasite load in AS and SS RBCs is the extent of oxidative damage which is inherent in these host cells added to the oxidative stress due to parasite growth; the cumulative oxidant damage can cause considerable damage to the host RBC and impairment of parasite development [39]. Interestingly, accumulated reactive oxygen species (ROS)-mediated damage is a common mechanism shared by AS, SS, G6PD-deficient, βand α-thalassemia RBCs in mediating resistance to malaria [40,41].…”
Section: Natural Resistance Against Blood-borne Parasitesmentioning
confidence: 99%
“…Further, it has been shown that parasites are fragile and killed by these HbS polymers. A compelling cause of reduced parasite load in AS and SS RBCs is the extent of oxidative damage which is inherent in these host cells added to the oxidative stress due to parasite growth; the cumulative oxidant damage can cause considerable damage to the host RBC and impairment of parasite development [39]. Interestingly, accumulated reactive oxygen species (ROS)-mediated damage is a common mechanism shared by AS, SS, G6PD-deficient, βand α-thalassemia RBCs in mediating resistance to malaria [40,41].…”
Section: Natural Resistance Against Blood-borne Parasitesmentioning
confidence: 99%
“…The hydroperoxides themselves are not very reactive but are readily converted in the presence of free iron and electron donor molecules to alkoxyl and hydroxyl radicals, which indiscriminately inflict damage on biomolecules. Intraerythrocyte parasites produce additional ROS [3,4]. Apart from ROS coming from inside the cells, erythrocytes may be exposed to ROS generated in tissues they contact.…”
Section: Introductionmentioning
confidence: 99%
“…Intraerythrocyte parasites produce additional ROS [3,4]. Apart from ROS coming from inside the cells, erythrocytes may be exposed to ROS generated in tissues they contact.…”
Section: Introductionmentioning
confidence: 99%